Does Foreign Currency Derivatives Hedging Increase Company Value? An Examination of UK Companies - Chen, Rishan (2018)
This paper investigates the determinants and effects of the use of foreign currency derivatives. The sample contains 402 UK firms during 2016-2017 fiscal year. Univariate and multivariate tests suggest that larger firms, firms with higher leverage level, firms with greater foreign exchange exposure are more likely to hedge. In addition, firms with lower level of liquidity and firms with smaller growth opportunities are more likely to hedge as well. Regression results of the effects of foreign currency hedging indicate that companies with international trading would probably have higher firm value, better performance of ROA and ROE, with the use of FCDs.